Lactobacillus reuteri growth and fermentation under high pressure towards the production of 1,3-propanediol - Mota, Maria J. (2018)
Lactobacillus reuteri is a lactic acid bacterium able to produce several relevant bio-based compounds, including 1,3-propanediol (1,3-PDO), a compound used in food industry for a wide range of purposes. The performance of fermentations under high pressure (HP) is a novel strategy for stimulation of microbial growth and possible improvement of fermentation processes. Therefore, the present work intended to evaluate the effects of HP (10–35 MPa) on L. reuteri growth and glycerol/glucose co-fermentation, particularly on 1,3-PDO production. Two different types of samples were used: with or without acetate added in the culture medium. The production of 1,3-PDO was stimulated at 10 MPa, resulting in enhanced final titers, yields and productivities, compared to 0.1 MPa. The highest 1,3-PDO titer (4.21 g L−1) was obtained in the presence of acetate at 10 MPa, representing yield and productivity improvements of ≈ 11 and 12%, respectively, relatively to the same samples at 0.1 MPa. In the absence of acetate, 1,3-PDO titer and productivity were similar to 0.1 MPa, but the yield increased≈26%. High pressure also affected the formation of by-products (lactate, acetate and ethanol) and, as a consequence, higher molar ratios 1,3-PDO:by-products were achieved at 10 MPa, regardless of the presence/absence of acetate. This indicates a metabolic shift, with modification of product selectivity towards production of 1,3-PDO. Overall, this work suggests that HP can be a useful tool to improve of 1,3-PDO production from glycerol by L. reuteri, even if proper process optimization and scale-up are still needed to allow its industrial application. It also opens the possibility of using this technology to stimulate other glycerol fermentations processes that are relevant for food science and biotechnology.